- DOMINASI KEKUASAAN DALAM MEDIA MENGENAI RUU TNI - Emilia Veti Rindi Vebiani; Erika Dwi Sabrina Putri; Rusdhianti Wuryaningrum (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2025)
Language in media discourse is not merely a tool of communication but an arena for the reproduction of power and ideology that shapes socio-political reality. The aim of this research is to reveal how textual structures, social cognition, and social context shape the construction of legislative discourse and influence public perceptions of the legitimacy of the DPR (House of Representatives) and the TNI. This research employs a descriptive qualitative method, with news texts as the primary data source, complemented by supporting literature to strengthen contextual interpretation. The findings show that Detik.com frames the enactment of the TNI Bill by emphasizing the formal legitimacy of the DPR through macrostructure, superstructure, and microstructure, including lexical choices, the use of passive constructions, and the omission of dominant actors. The voices of civil society and public protest are presented only in a limited manner, while government actors are foregrounded, directing readers to accept the legislative decision as legitimate and final. The analysis of social cognition reveals that the media shapes collective understandings regarding the legitimacy of state institutions, whereas the social context dimension shows an asymmetrical power relationship between the government and civil society. These findings affirm that media discourse production is not a neutral activity but an ideological instrument to reproduce power domination and control public opinion. This research enhances comprehension of online media discourse regarding military legislation, emphasizing the impact of microstructural strategies and framing on public perception. The findings are expected to serve as a basis for future research to explore cross-media news comparisons, public responses via social media, and the dynamics of legal legitimacy in the context of Indonesian democracy.